Opportunity Costs, Cognitive Biases, and Autism - Sergio Da Silva; Maria Fiebig; Raul Matsushita (Journal of Mind and Medical Sciences, 2025)
Do individuals with autism overlook opportunity costs? Considering the mediating role of cognitive biases and utilizing an AI-driven experiment, our provisional answer is yes. Cognitive biases can severely distort the accurate calculation of opportunity costs, which is essential for making optimal decisions by clearly understanding the trade-offs involved in pursuing a particular course of action. In turn, biased information processing may contribute to developmental disorders such as autism that are marked by difficulties with social interaction, communication, and restricted or repetitive behaviors. We developed a 20-question scale to assess the neglect of opportunity costs, targeting specific cognitive biases, and compared the results with the RAADS-R autism scale. We find that individuals scoring low on the opportunity cost scale, due to these cognitive biases, are likely to score higher on the RAADS-R, aligning their decision-making biases with traits typical of the autism spectrum.